Stability analysis of rice (Oryza sativa L.) genotypes with high grain zinc in five different locations of Eastern Uttar Pradesh - Singh, S. K.; Behera, Partha Pratim; Singh, D. K.; Korada, Mounika; Habde, Sonali Vijay; Khaire, Amrutlal (Hooghly: Sciencedomain International, 2020)
Rice is a major energy source food crop and a staple food for more than half of the world’s population. The knowledge of mean performance and stability of high grain Zinc rice genotypes from a multi-location trial is a way to assess the genotypes so as to achieve food and nutritional security. The present research was conducted to study the stability of 21 high grain Zinc rice genotypes for thirteen yield and yield attributing traits in RCBD with 3 replications in five different locations of Eastern Uttar Pradesh using the Eberhart and Russell stability model. Based on the environmental index, Bhikaripur village is identified as the most favourable environment. The inspection of stability and ANOVA revealed that there were significant linear G x E interactions for most of the characters studied expect plant height, spikelet fertility % and total effective tiller number which implied that there were significant variations among the genotypes. The environment + (genotype x environment) was significant for most of the traits except grain L/B ratio representing specific nature of environments and G x E interaction in morphological expression. Based on the stability parameters none of the genotypes could be identified as stable for any traits over the five environments but, IR 97443-11-2-1-1-1-1 –B and Local check (HUR3022) showed stability for high yield in all the environments. The genotype, IR 97443-11-2-1-1-1-1 –B having stability for grain yield per ha with higher mean and short duration, is also stable for grain yield per plant, grain weight per panicle and spikelet fertility % and could be used as high yielding cultivar and can be used as a parent in future breeding programs. The genotype, IR 95044:8-B-5-22-19-GBS is having the highest grain Zinc content. High grain zinc with higher yield was reported in BRRIdhan 64 and it is stable for grain zinc content and can be used for Zinc bio-fortification breeding programs to minimize malnutrition to ensure food and nutritional security.